Analytical Study: The Effectiveness of Emergency Response Training in Enhancing Community Competence Along Tuban’s North Coast Route - Moh. Ubaidillah Faqih; Karyo; Dwi Kurnia Purnama Sari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background : Traffic accidents along the North Coast Route (Pantura) in Tuban, East Java, remain a major public health concern, often leading to severe injuries and fatalities due to delays in early emergency response at the scene. Limited community capacity in providing first aid highlights the urgent need for effective training interventions. This study aimed to evaluate the effectiveness of simulation-based emergency response training in improving knowledge, attitudes, and practical skills among adolescents living in high-risk areas. Methods : A quantitative quasi-experimental study with a one-group pretest–posttest design was conducted among 155 adolescents aged 15–18 years selected using cluster random sampling across five high-risk areas. The intervention consisted of four training sessions delivered within one week, combining lectures, demonstrations, and scenario-based simulations covering CPR, bleeding control, and victim evacuation. Data were collected using validated questionnaires and observation checklists before and after the intervention. Statistical analysis was performed using paired-sample t-test with a significance level of p < 0.05. Results: Knowledge scores increased from 56.3 to 82.7, attitude scores from 60.1 to 84.2, and practical skills scores from 48.5 to 79.9, all showing statistically significant improvements (p < 0.001). Conclusions: Simulation-based emergency training significantly improves community capacity in emergency response, particularly in practical skills. This approach is recommended as a scalable strategy to strengthen early emergency management in accident-prone areas and reduce preventable morbidity and mortality.